Six principaux freins à l'engagement des apprenants dans les forums de discussion des MOOC de l'université de Genève. Un diagnostic pour mieux soutenir les interactions dans les MOOC - Yannick Stéphane Nleme Ze; Gaëlle Molinari (Centre National d'Enseignement à Distance, 2023)
This quantitative study carried out among 303 learners of 8 MOOCs from the University of Geneva highlights 6 main factors that prevent and limit their engagement in the discussion forums of these courses. This diagnosis will feed future research that will design intelligent systems that can manage MOOC forums or simply replacing them in order to allow synchronous communication experienced as natural and "real" by learners.